Comparative study of USG guided aspiration and non-aspiration cytology for evaluation of specimen quality and diagnostic accuracy in abdominal and pelvic lumps - Dr Archana Bundela; Dr AlpanaBundela; Dr Shilpa U. Vahikar; Dr. Kanchan Srivastava (Tropical Journal of Pathology and Microbiology, 2018)
Introduction: The aim of this study was to compare the efficacy of USG guided fine needle aspiration cytology (FNAC) with that of fine needle non aspiration cytology (FNNAC) in abdominal, pelvic masses. Objectives: Although a large volume of data is available to compare FNAC and FNNAC sampling in superficial lesions, very less literature is available regarding FNNAC for abdominal and pelvic masses. Therefore we have directly compared the diagnostic accuracy and specimen quality of both techniques FNAC and FNNAC under guidance of ultrasound in intra abdominal and pelvic mass lesions. Method: Samples were obtained by applying both FNAC and FNNAC techniques for abdominal, pelvic lumps of 71 patients who attended the pathology department of BRD Medical College Gorakhpur, Uttar Pradesh. The sampling procedure were done by single operator, smears made from FNAC and FNNAC techniques were studied using a objective scoring system based on the background blood or clot, amount of cellular material, degree of cellular degeneration, degree of cellular trauma and retention of appropriate architecture and then comparison of diagnosed case was done with histopathology. Results: The overall diagnostic accuracy was 85.9% in FNAC and 83.0% in FNNAC(p=0.80).Diagnostic accuracy by FNAC are 83.3%,92.8%,91.6% in cases of liver,gallbladder and ovary respectively. In cases of G.I.T masses it is 81.9% by FNAC.Diagnostic accuracy by FNNAC it is maximum 93.4% in cases of liver masses and lower in ovarian masses (66.6%) when compared with the histopathology. A statistically insignificant difference was recorded in sampling technique score for quality of smears in all cases except in the liver where the FNNAC score was statistically significant. Conclusion: Although both techniques have their own advantages and disadvantages but diagnostic accuracy was much better by FNAC than FNNAC but quality of smears for cytodiagnosis was superior by FNNAC technique than FNAC in all abdominal, pelvic masses.